2008
DOI: 10.1136/jnnp.2008.143693
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system involvement in Anderson-Fabry disease: a clinical and MRI retrospective study

Abstract: The study demonstrated a high frequency of CNS involvement in homozygous and heterozygous AFD patients, often characterised by early age at onset and abnormal brain MRIs. At present, ERT is widely used; however, potential beneficent effects may be disguised by the progression of irreversible pathology in short-term follow-up. Therefore, primary and secondary prophylaxes of cerebrovascular disease are extremely important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
2
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 36 publications
3
78
2
6
Order By: Relevance
“…20 In patients with Fabry-related stroke, the neurological symptoms experienced are normally consistent with the vascular territory affected and the extent of the stroke. 2 Although many patients have clear neuroradiological findings on MRI, the causes of clinically asymptomatic brain lesions and chronic white matter hyperintensities (CWMH) in Fabry patients remain controversial.…”
Section: Stroke Prevalence Age At Onset and Influence Of Sexmentioning
confidence: 98%
See 1 more Smart Citation
“…20 In patients with Fabry-related stroke, the neurological symptoms experienced are normally consistent with the vascular territory affected and the extent of the stroke. 2 Although many patients have clear neuroradiological findings on MRI, the causes of clinically asymptomatic brain lesions and chronic white matter hyperintensities (CWMH) in Fabry patients remain controversial.…”
Section: Stroke Prevalence Age At Onset and Influence Of Sexmentioning
confidence: 98%
“…20,[24][25][26][27] Data from the Fabry Registry reported that women with FD were more likely to experience a stroke than men with FD 10 although female patients were likely to be older at first stroke. 10,20,27 However, hemorrhagic stroke has also been reported to be more common among men than women with FD (16.9% versus 6.9%, respectively). 10 The observed differences in cerebrovascular involvement among male and female Fabry patients are difficult to explain.…”
Section: Stroke Prevalence Age At Onset and Influence Of Sexmentioning
confidence: 99%
“…Recently, it is reported that cerebral small artery disease, which is known to be associated with lacunar infarction, white matter lesions (leukoaraiosis) and cerebral hemorrhage, rather than large artery stroke, is frequently observed in Fabry's disease. 5,6,20 These findings suggest that the underlying degeneration of the cerebral small arteries, secondary to the deposition of glycosphingolipids in the vessel wall, could be a strong contributing factor for cerebral hemorrhage in Fabry's disease. Aging is thought to be another important contributing factor, 6 as our patients, especially patients 2 (83 years old) and 3 (74 years old), were elderly compared with average Fabry's patients.…”
Section: Discussionmentioning
confidence: 89%
“…1 Stroke is one of the major complications of Fabry's disease 2 and has been described in X25% of patients. [3][4][5][6] In patients with the classic phenotype, levels of a-Gal A activity are very low or undetectable, and progressive glycosphingolipids accumulation leads to renal, cardiac and cerebrovascular manifestations and early death. 1 On the other hand, patients with substantial levels of residual a-Gal A activity have milder phenotypes, including renal 7 and cardiac 8 variant.…”
Section: Introductionmentioning
confidence: 99%
“…Agalsidase alpha has been shown to stabilize, and possibly improve vestibular function (44) and hearing in Fabry patients who have not already progressed to severe hearing loss (45). However, patients suffering from cerebrovascular disease have not shown a significant improvement after treatment (46).…”
Section: Heterozygotesmentioning
confidence: 99%